Pengaruh Costumer Relationship Management, Keamanan Layanan terhadap Kepuasan Nasabah dan Loyalitas Nasabah dalam Penggunaan Mobile Banking pada PT. Bank Mandiri Tbk Cabang Takalar - Mardaniar, Andi; Mappatompo, Andi; Romadhoni, Buyung (Ekonomis: Journal of Economics and Business, 2025)
This study aims to evaluate the effectiveness of targeted policies including customer relationship management, service security schemes to minimize user concerns about misuse of personal data in encouraging customer satisfaction in using mobile banking. The quantitative method approach uses a questionnaire as a source of data collection. This study used 200 respondents using the path analysis technique. The results showed that customer relationship management has a positive but insignificant effect on customer satisfaction, but service security has a significant positive effect on customer satisfaction. This finding suggests that a more consistent customer relationship management framework is essential to optimize the contribution of customer satisfaction. This study highlights the potential for highly effective customer feedback data and information management and can be used as a basis for knowing what customers need in order to achieve maximum customer satisfaction.